Media Pembelajaran Interaktif Matematika Berbasis Flash Pada Siswa Kelas 1 MI NW Liqaul Amal - Yupi Kuspandi Putra; Muhamad Sadali; Irwan Hadi (Fakultas Teknik Universitas Hamzanwadi, 2021)
The purpose of this study is to facilitate teaching and learning activities, so that it can improve students' understanding of the mathematics material presented by the teacher and can be used as a medium to increase interest and interest in the learning process. Learning media plays an important role in teaching and learning activities so that the teaching and learning process becomes effective and easy to apply, but in reality in the world of education learning media is often not paid attention to because of limited time to make teaching preparation and it is difficult to find the right media. At MI NW Liqaul Amal still using manual learning media using books, writing and other teaching aids as student learning tools, learning media like this still cannot increase student interest, especially in mathematics lessons. One of the learning methods used to overcome these problems is to create interactive learning media in mathematics subjects. This learning media starts with a needs analysis process that will be used in making flash-based interactive learning media and making concepts or designs according to the results of the analysis. The results to be achieved in making interactive learning media on mathematics subjects are that students can understand the material and increase student interest in learning, so that the teaching and learning process becomes more effective.